FORMULASI MOUTHWASH EKSTRAK ECENG GONDOK (Eichhornia crassipes (Mart.) Solms) SEBAGAI ANTIBAKTERI KARIES GIGI (Streptococcus mutans) - Fadillah Djafar; Paulina V.Y. Yamlean; Jainer P. Siampa (PHARMACON, 2021)
ABSTRACTWater hyacinth (Eichhornia crassipes (Mart.) Solms) contains compounds such as saponins, flavonoids, polyphenols, and alkaloids which have antibacterial properties. This study aims to make a mouthwash formulation for water hyacinth extract (E. crassipes) and to test the antibacterial activity of the preparation with an extract concentration of 5%, 10%, and 15% against the growth of Streptococcus mutans bacteria. This research uses experimental methods. The preparation formula for water hyacinth extract (E.crassipes) mouthwash is then carried out by quality testing which includes testing for organoleptic, pH, homogeneity, sedimentation test, and determination of density. The diffusion method was used to test the antibacterial activity against S. mutans growth. The results of the test of the quality of the preparations are stated in accordance with the standards. Mouthwash that has been defined, which has a clear color, distinctive smell of menthol and sweet, with a pH of 6,16; 6, 13; and 6,12. The preparations were also homogeneous without precipitates or coarse grains, the density in formulations 1, 2, and 3 was 1, 0245; 1, 0251; 1, 0253. The results of testing the antibacterial activity of water hyacinth leaf infusion extract with a concentration of 5%, 10%, and 15% showed that there was antibacterial activity, and the highest activity was at a concentration of 15% with a strong category. Keywords: Mouthwash, Water Hyacinth, Infundation, Antibacterial.  ABSTRAKEceng Gondok (Eichhornia crassipes (Mart.) Solms) memiliki kandungan senyawa saponin, flavonoid, polifenol, dan alkaloid yang bersifat sebagai antibakteri. Penelitian ini bertujuan untuk membuat formula sediaan mouthwash  ekstrak Eceng Gondok (E. crassipes) serta menguji aktivitas antibakteri sediaan dengan konsentrasi ekstrak 5%, 10%, dan 15% terhadap pertumbuhan bakteri Streptococcus mutans. Penelitian ini menggunakan metode eksperimental. Formula sediaan mouthwash ekstrak Eceng Gondok (E.crassipes) ini kemudian dilakukan pengujian mutu yang meliputi pengujian organoleptik, pH, homogenitas, uji sedimentasi, dan penetapan massa jenis. Pengujian aktivitas antibakteri terhadap pertumbuhan S.mutans dilakukan dengan metode difusi. Hasil dari uji mutu sediaan dinyatakan sesuai dengan standar Mouthwash yang ditetapkan, yakni memiliki warna yang jernih, bau khas menthol dan manis, dengan pH 6, 16; 6, 13; dan 6, 12. Sediaan juga homogen tanpa  endapan maupun butiran kasar, massa jenis pada formulasi 1, 2, dan 3 adalah 1, 0245; 1, 0251; 1, 0253.  Hasil pengujian aktivitas antibakteri ekstrak infusa daun Eceng Gondok konsentrasi 5%, 10%, dan 15% menunjukkan adanya aktivitas antibakteri, dan aktivitas tertinggi terdapat pada konsentrasi 15% dengan kategori kuat.Kata kunci: Mouthwash, Eceng Gondok, Infundasi, Antibakteri.